DEVELOPMENT OF THE CONCEPT OF RELATIONSHIP MARKETING (INNOVATIVE ECONOMY, 2025)
Lytiuk D.S.  DEVELOPMENT OF THE CONCEPT OF RELATIONSHIP MARKETINGPurpose. The aim of the study is to analyse the evolution of the concept of relationship marketing, identify its key characteristics, principles, and significance for modern enterprises, and substantiate the role of customer relationship management (CRM) as a strategic tool for enhancing the competitiveness of enterprises. Methodology of research. A comprehensive approach was used to achieve the stated purpose: literature analysis – to trace the prerequisites for the emergence, main development stages, and conceptualization of relationship marketing; comparative analysis – to distinguish between the concepts of “relationship marketing,” “partnership marketing,” and “loyalty marketing,” and to define key characteristics and principles of relationship marketing in comparison with transactional marketing; system analysis of CRM and Relationship Marketing Tools – to determine their impact on customer loyalty, profitability, and competitive advantage. This methodology allows the alignment of theoretical concepts with practical results of implementing relationship marketing in contemporary business conditions, particularly in Ukraine.Findings. The study establishes that relationship marketing functions as a strategic management philosophy that ensures the transition from short-term transactions to long-term mutually beneficial relationships with all key stakeholders. The main characteristics of this approach are identified, including long-term orientation, mutual benefit, trust, cooperation and consumer orientation.The role of CRM systems and the concept of customer lifecycle value (CLV) in increasing the efficiency of business processes, personalizing offers, and building customer loyalty are analysed. It is substantiated that the use of affiliate marketing enables companies to optimize interactions with suppliers and distributors, reduce risks, increase profitability, and create long-term competitive advantages.Originality. The scientific novelty lies in the generalization and systematization of approaches to relationship marketing through the integration of three key components: CRM management, Customer Lifetime Value (CLV) concept, and partnership marketing. The study substantiates that their combined application ensures the formation of long-term mutually beneficial relationships with stakeholders and contributes to enhancing the competitiveness of enterprises in the current market conditions.Practical value. The proposed relationship marketing tools can be implemented in enterprises across various sectors (industry, agriculture, trade, and services) to increase customer loyalty, optimize business processes, enhance profitability, and strengthen market positions. Utilizing CRM, CLV, and partnership marketing allows the creation of an integrated strategy that ensures long-term competitiveness and stability of the enterprise.Key words: relationship marketing, transactional marketing, customer relationship management, loyalty, partnership, evolution of marketing.
Keywords: relationship marketing; transactional marketing; customer relationship management; loyalty; partnership; evolution of marketing